UPAYA MENINGKATKAN RASA INGIN TAHU DAN PRESTASI BELAJAR ILMU PENGETAHUAN ALAM MATERI PEMBENTUKAN TANAH MELALUI MODEL PEMBELAJARAN MAKE A MATCH - Isnarofik, Maulana Bayu (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
On science learning at fifth grade SD Negeri 2 Kotayasa showed that learning process still used lecturing method and lack of students’ participation. The research was aimed at improving curiosity and science learning achievement at class V SD Negeri 2 Kotayasa. The research was done in 2 cycles which consisted of 2 meetings for each. The result of the research showed that there was an improvement. The average of curiosity in cycle I was 30,3. Meanwhile, the average of curiosity in cycle 122,2 and for cycle II there was an improvement on which the average was 159 with 81,5% as the classical completeness. Based on the data aforementioned, it could be concluded that make a match learning model could improve curiosity and science learning achievement on land forming material through making a match learning model in class V SD Negeri 2 Kotayasa. This classroom action research improved curiosity and science learning model on land forming through make a match learning model.